Siringomiyeliye bağlı el-el bileği nöropatik artropatisi: Olgu sunumu - (:unkn) unknown (My University, 2009)
Nöropatik artropati, periferik veya omurga eklemlerini etkileyen, altta yatan santral veya periferik nörolojik hastalık ile bağlantılı progresif, dejeneratif bir artrittir. En sık nedenleri diyabetes mellitus ve sifilizdir. Syringomyeli spinal kordun kronik, progresif dejeneratif veya gelişimsel bir hastalığıdır ve nadiren üst ekstremitelerde nöropatik artropatiye neden olabilir. Bu yazıda siringomyeliye sekonder gelişen, el bileği nöropatik artropatili bir olgu sunulmuştur.

Neuropathic arthropathy is a progressive, degenerative arthritis affecting one or more peripheral or vertebral articulations and is associated with an underlying central or peripheral neurological disorder. Diabetes mellitus and syphilis are among the most common causes of the neuropathic arthropathy. Syringomyelia is a chronic progressive degenerative or developmental disorder of the spinal cord and may lead to neuropathic arthropathy in the upper extremities. Herein, we report a case of neuropathic arthropathy with wrist involvement secondary to syringomyelia.
Case report: Wrist neuropathic arthropathy secondary to syringomyelia
Keywords: Geriatri ve Gerontoloji; Pediatri